Classical and modern concepts of corporate governance (Stewardship Theory and Agency Theory) = Klasyczne i współczesne koncepcje nadzoru korporacyjnego (teoria agencji i Stewarda) - Glinkowska, Beata; Kaczmarek, Bogusław (Zielona Góra: Faculty of Economics and Management Press)
The main issues in efficiency of a company as an organisation are relations between the Supervisory Board and the Management Board of a company, and the methods of functioning of Supervisory Boards in governance systems of a company. The classical and modern approach to the role, place, and importance of corporate governance presented in this article, is yet another prompt to continue searching for the optimum in the organisational, economical, and social meaning.
Keywords: nadzór korporacyjny; rada nadzorcza; sprawność działania; teoria agencji; teoria Stewarda; corporate governance; supervisory of board; Agency Theory; Stewardship Theory